Determination of the list of basic construction resources for the analysis of prices for the construction of the Lviv stadium for Euro 2012. - Sichnyi, S.B (Ways to Improve Construction Efficiency, 2021)
Since 2009, Ukraine has gradually introduced requirements for the minimum level of prices for construction resources, which are set on the basis of its own (construction participants) data bank and market analysis. However, the procedure for creating, filling and maintaining such data banks is not regulated, as well as the method of market analysis and the procedure for determining the lowest market price of construction resources. The article considers the sequence of formation of the list of construction resources for inclusion in the data bank during the implementation and launch of the analysis of current prices in the market of construction resources. Organizational, technical and methodological problems and approaches to their solution are highlighted. The example of the construction of the Lviv stadium for Euro 2012 shows the features of the initial data for the formation of a list of resources for inclusion in the bank of price data and the sequence of their completion, the need for which is dictated by the specifics of domestic design and construction. An algorithm for determining the initial list of construction resources is proposed and the sequence of its execution is considered on an example. Methods for reducing the initial list of construction resources by including only those resources that are essential for determining the total market value of construction resources on any structure are proposed. Namely: pricing material resources and resources that represent groups of homogeneous, similar, resources, from the point of view of the supplier, and are in the same price range (representative resources). A universal methodology for determining pricing resources is proposed and an example of its application is given. A universal methodology for determining generalizing resources (representative resources) for similar materials that have different estimate codes, but equal technical and qualitative characteristics and are in the same price range. An example of its application is given. The set of proposed measures and methods allowed to reduce the total number of positions in the source documents from 4580 to 203 basic resources placed in the database of current prices in the market of construction resources during the construction of the Lviv stadium for Euro-2012. The actual number of construction materials for which price analysis was performed amounted to 309 items with a total value of 98% of the total cost of construction materials of the consolidated statement of resources, with a given threshold of 96%. Labor costs at the stage of launching the price analysis decreased by 77.5% or 4.4 times. Labor costs at the stage of market price analysis decreased by 34.3% or 1.5 times. At the same time, the accuracy of calculations remained within the statistical error.